France : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 1998)
This Selected Issues paper and Statistical Appendix presents a set of generational accounts to contribute to the assessment of France's long-term fiscal position. The generational accounting framework is outlined, followed by a discussion of its major limitations. The specific case of France, including the construction of the accounts, a discussion of key parameters used, and the main findings are presented. The paper places France's generational policy in an international perspective. The lifetime net tax payments of current adults are calculated and compared with those of younger living generations.